Analisis Literatur Tentang Fisika Suprakonduktor Aplikasinya Dalam Teknologi Energi - Harefa, Febrianus; Zalukhu, Enjel Pujaan (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
The physics of superconductors is a significant branch of physics, especially in the innovation of energy technology. Superconductors, which can conduct electricity without resistance at certain temperatures, have opened up vast opportunities for the development of efficient energy technology. This article aims to examine the progress of research in superconducting physics and its applications, particularly in the energy technology sector. From the existing literature review, superconductors have shown great potential in energy technology applications, such as electrical transmission cables, energy storage, and sustainable power generation